Analysis of Ethical Principles and Rules of Public Employees - R.B. Khodaparasti (University of Sofia, 2012)
This paper aims to identify factors influencing the ethical behavior of people in public or private organizations. Generally, ethics is as a system of values, allowing the organizations to be distinguished as bad or good. In order to investigate the ethical principles, the Charter of the Square Model is used in this study. The statistical sample includes 145 men and women who have been summoned from three types of structures: irrigation management, telecommunications, and City Hall of Urmia (Iran). Results show that the three factors considered in the study - the administrative regulations and employment laws and principles; beliefs and behaviors of clients; and knowledge of the principles and provisions of the Code of Ethics, affect employees, and therefore, special attention should be focused on these three issues.